Peran Hukum dalam Meningkatkan Partisipasi Publik pada Pemerintahan Daerah - Lidia Rumapea; Margaret Pangaribuan; Muthia Ivana Zhara; Moria Debora Siahaan; Putri Intan Siringo Ringo; Sri Hadiningrum; Parlaungan Siahaan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Law plays a crucial role in enhancing public participation in local governance by providing a clear framework for citizen engagement in decision-making, oversight, and the fulfillment of their rights. This study examines the application of legal frameworks to improve public involvement in regional governance, focusing on the Indonesian context. Using an empirical juridical method, the research combines normative analysis of laws and empirical data from interviews and observations. Findings reveal that responsive legal products and participatory processes are essential to fostering public engagement in regional development. Key challenges include limited public awareness, bureaucratic inefficiencies, and inconsistent implementation of legal provisions. Addressing these issues through public education, transparent governance, and stronger legal enforcement can significantly improve participation rates. This paper highlights the importance of integrating legal and social perspectives to create inclusive and effective governance at the local level.